Feeding Pre-weaned Calves With Waste Milk Containing Antibiotic Residues Is Related to a Higher Incidence of Diarrhea and Alterations in the Fecal Microbiota - Penati, Martina; Sala, Giulia; Biscarini, Filippo; Boccardo, Antonio; Bronzo, Valerio; Castiglioni, Bianca; Cremonesi, Paola; Moroni, Paolo; Pravettoni, Davide; Addis, Maria Filippa (Frontiers in Veterinary Science, 2021)
The cows receiving antibiotics for intramammary infection (IMI) produce milk that cannot be marketed. This is considered waste milk (WM), and a convenient option for farmers is using it as calf food. However, adding to the risk of selecting resistant bacteria, residual antibiotics might interfere with the gut microbiome development and influence gastrointestinal health. We assessed the longitudinal effect of unpasteurized WM containing residual cephalexin on the calf intestinal health and fecal microbiota in an 8-week trial. After 3 days of colostrum, 6 calves received WM and 6 bulk tank milk (BM) for 2 weeks. For the following 6 weeks, all 12 calves received milk substitute and starter feed. Every week for the first 2 weeks, and every 2 weeks for the remaining 6 weeks, we subjected all calves to clinical examination and collected rectal swabs for investigating the fecal microbiota composition. Most WM calves had diarrhea episodes in the first two weeks of the trial (5/6 WM and 1/6 BM), and their body weight was significantly lower than BM calves. Based on 16S rRNA gene analysis, WM calves had a lower fecal microbiota alpha-diversity than BM calves, with the lowest p-value at Wk4 (p < 0.02), two weeks after exposure to WM. The fecal microbiota beta-diversity of the two calf groups was also significantly different at Wk4 (p < 0.05). Numerous significant differences were present in the fecal microbiota taxonomy of WM and BM calves in terms of relative normalized OTU levels, affecting 5 phyla, 7 classes, 8 orders, 19 families, and 47 genera. At the end of the trial, when 6 weeks had passed since exposure to WM, the phyla Bacteroidetes, Firmicutes, and Saccharibacteria were lower while Chlamydiae were higher in WM calves. Notably, WM calves showed a decrease in beneficial taxa such as Faecalibacterium, with a concomitant increase in potential pathogens such as Campylobacter, Pseudomonas, and Chlamydophila. In conclusion, feeding pre-weaned calves with unpasteurized WM containing antibiotics is related to a higher incidence of neonatal diarrhea and leads to significant changes in the fecal microbiota composition, further discouraging this practice in spite of its short-term economic advantages.